Relationship between training-induced changes in the star excursion balance test and the Y- balance test in young male athletes - Mohammadi, V.; Hilfiker, R.; Jafarnezhadgero, A. A.; Jamialahmadi, S.; Ardakani, M. K.; Granacher, U. (Annals of Applied Sport Science, 2017)
Background. Dynamic balance is often assessed in athletes using either the Star Excursion Balance Test (SEBT) or the Y Balance Test (YBT). There is evidence that the results for the three common directions are not comparable. Thus, the question is open to debate as to which instrument is better suited to measure training-induced changes over time. Objectives. The aim of this study is to compare the changes in the SEBT and the YBT, measured before and after six weeks of balance and strength exercise programmes in young and healthy athletes. Methods. A total of 30 young male athletes aged 15-17 years participated in this study and were involved in a six-week combined training, including balance and strength exercise. During pre- and post-training periods, the SEBT and YBT were conducted in random order. Results. The comparison between the changes in the SEBT and YBT with a paired sample T-test showed a significant increase in PM (p=0.001) and PL reach directions (p=0.000). No differences were observed in the A reach direction (p=0.38). Conclusion. the responsiveness levels of the SEBT and YBT are similar is valid. Also, because of higher effect size value in the anterior direction in YBT compared with SEBT, this balance test could possibly be preferred in this direction for postural control evaluation.